Zooming in on the circumgalactic medium with GIBLE: resolving small-scale gas structure in cosmological simulations - Ramesh, Rahul; Nelson, Dylan (Monthly notices of the Royal Astronomical Society, 2024)
We introduce Project GIBLE (Gas Is Better resoLved around galaxiEs), a suite of cosmological zoom-in simulations where gas in the circumgalactic medium (CGM) is preferentially simulated at ultra-high numerical resolution. Our initial sample consists of eight galaxies, all selected as Milky Way-like galaxies at z = 0 from the TNG50 simulation. Using the same galaxy formation model as IllustrisTNG, and the moving-mesh code arepo, we re-simulate each of these eight galaxies maintaining a resolution equivalent to TNG50-2 (mgas ∼ 8 × 105 M⊙). However, we use our super-Lagrangian refinement scheme to more finely resolve gas in the CGM around these galaxies. Our highest resolution runs achieve 512 times better mass resolution (∼103 M⊙). This corresponds to a median spatial resolution of ∼75 pc at 0.15 R200, c, which coarsens with increasing distance to ∼700 pc at the virial radius. We make predictions for the covering fractions of several observational tracers of multiphase CGM gas: H i, Mg ii, C iv, and O vii. We then study the impact of improved resolution on small scale structure. While the abundance of the smallest cold, dense gas clouds continues to increase with improving resolution, the number of massive clouds is well converged. We conclude by quantifying small scale structure with the velocity structure function and the autocorrelation function of the density field, assessing their resolution dependence. The GIBLE cosmological hydrodynamical simulations enable us to improve resolution in a computationally efficient manner, thereby achieving numerical convergence of a subset of key CGM gas properties and observables.